2011
DOI: 10.1007/s00405-011-1871-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral aplasia of paranasal sinuses

Abstract: Paranasal sinus anatomical anomalies with unknown etiology are common. Maxillary and/or frontal sinus aplasia or hypoplasia are more common than the other types. Although there are some reports about paranasal sinus anomalies in the literature, there is no case similar to ours, with total paranasal sinus aplasia. Here, we present a unique case of total paranasal sinus aplasia with a symptom of fullness on the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…9 His major symptom was fullness of the face, which was also described by our patient. He did not have headache and masticatory problems.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…9 His major symptom was fullness of the face, which was also described by our patient. He did not have headache and masticatory problems.…”
Section: Discussionsupporting
confidence: 82%
“…To the best of our knowledge, this is the second case report of total paranasal sinus aplasia in the English language literature. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Celebi et al reported total aplasia of PNS in 2012. 5 Hakan Korkmaz et al Reported total aplasia of PNS in 2013. 6 Concluding, we have to be aware of any of these rare morphological alternatives while treating sinus patho logy to reach correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is rudimentary at birth and reaches adult size at puberty following the eruption of permanent teeth, with a mean volume of 12.5 ml [8]. It may occasionally be absent or hypoplastic [3]. The functions of the maxillary sinus are controversial, but it is said to include reduction in weight of the craniofacial bones, acts as a shock absorber to traumatic forces, thermal insulation, humidification, and warming of inspired air, and influences facial growth [25].…”
Section: O R I G I N a L Pa P E Rmentioning
confidence: 99%